Analysis of Genetic Variation in the Bovine SLC11A1 Gene, Its Influence on the Expression of NRAMP1 and Potential Association With Resistance to Bovine Tuberculosis - Holder, Angela; Garty, Rachel; Elder, Charlotte; Mesnard, Paula; Laquerbe, Celine; Bartens, Marie-Christine; Salavati, Mazdak; Shabbir, Muhammad Zubair; Tzelos, Thomas; Connelly, Timothy; Villarreal-Ramos, Bernardo; Werling, Dirk (Frontiers in Microbiology, 2020)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a chronic zoonotic disease where host genetics is thought to contribute to susceptibility or resistance. One of the genes implicated is the SLC11A1 gene, that encodes for the natural resistance-associated macrophage protein 1 (NRAMP1). The aim of this study was to identify SLC11A1 polymorphisms and to investigate any resulting functional differences in NRAMP1 expression that might be correlated with resistance/susceptibility to M. bovis infection. Sequencing of the SLC11A1 gene in cDNA isolated from Brown Swiss, Holstein Friesian, and Sahiwal cattle identified five single nucleotide polymorphisms (SNPs) in the coding region, but only one of these (SNP4, c.1066C>G, rs109453173) was present in all three cattle breeds and therefore warranted further investigation. Additionally, variations of 10, 11, and 12 GT repeats were identified in a microsatellite (MS1) in the SLC11A1 3′UTR. Measurement of NRAMP1 expression in bovine macrophages by ELISA showed no differences between cells generated from the different breeds. Furthermore, variations in the length of the MS1 microsatellite did not impact on NRAMP1 protein expression as analyzed by luciferase reporter assay. However, further analysis of the ELISA data identified that the presence of the alternative G allele at SNP4 was associated with increased expression of NRAMP1 in bovine macrophages. Since NRAMP1 has been shown to influence the survival of intracellular pathogens such as M. bovis through the sequestering of iron, it is possible that cattle expressing the alternative G allele might have an increased resistance to bTB through increased NRAMP1 expression in their macrophages.